Topos of Egypt in Poetry of Silver Age - S. Mulahi; E. N. Eltsova; S. M. Pinaev (Научный диалог, 2021)
The specificity of the development of the geographical and cultural space of Egypt in the poetry of the Silver Age at the time when the “Russian” poetic Egypt was born as a system of leitmotifs, imagestopos and a specific lexicon is described. It is noted that in modern literary criticism, in comprehending the geopoetics of a regional text, works devoted to the European continent, in particular, geopoetic regional models of Russian literature, have been most fully investigated. The relevance of the study is seen in the need to comprehend and analyze the geopoetics of Egypt and, more broadly, Africa as a sacred geocultural space. The textual fragments of poetic works by K. Balmont, V. Bryusov, I. Bunin, N. Gumilyov, V. Khlebnikov, representing stable geospatial images and symbols of Egypt, are analyzed. The authors come to the conclusion that the poetry of the Silver Age combines geocultural images and symbols with mythological motives, which gives the topos of Egypt a geosophical meaning. The analyzed material made it possible to show the generalized artistic structure of the geopoetic representation of Egypt in the poetics of the Silver Age and to highlight the spatial geocultural dominants: the  Nile, Africa, the desert, the Sphinx, Egyptian heroes as images-topos, the Arab East.